Thematic Evolution of Educational Technology Research: A Large-Scale Topic Modeling Perspective - Aslan, Alper; Akti Aslan, Seda; Turgut, Yigit Emrah; Allison, Jordan; Ozyurt, Ozcan (Sage Publications Inc, 2026)
This study aims to reveal the thematic evolution of the educational technology field by analyzing 17,393 articles published between 2000 and 2024 in ten leading journals using the Latent Dirichlet Allocation (LDA) based topic modeling. Based on the analysis of title, abstract, and keywords, 20 themes were identified and grouped under seven broader meta-themes such as Teacher Professional Competence and Technology Adoption, Digital and Disciplinary Literacy Development, and Immersive and Experiential Learning Technologies. The model achieved its highest coherence at K = 20 (c_v = 0.4091), and the stability of the thematic structure was supported through additional runs with alternative hyperparameter configurations and expert validation. The findings show that there has been a significant increase in themes such as Technology Integration, Teacher Roles in Online Learning Design, and Technology Acceptance and Self-Efficacy in recent years. Temporal trend and growth analyses indicate that these themes will continue to shape the research landscape in the upcoming years. This holistic approach, which overcomes the contextual limitations of traditional bibliometric analysis, makes a significant contribution to the literature by mapping the last 25 years of scholarly accumulation in educational technology.
Keywords: topic modeling; educational technology; latent dirichlet allocation; thematic evolution